The Role of Trust and Risk in Online Product Purchase Decisions: Study on Students of the D4 Department of International Business Administration - Marsinah, Marsinah (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the role of trust and perceived risk perception in influencing online product purchase decisions in D4 International Business Administration students. The approach is quantitative, using a Likert-scale questionnaire distributed to students who are actively shopping online. Data were analyzed using multiple linear regression to test the partial and simultaneous influences of the variables. The results showed that trust had a positive and significant effect on purchase decisions, while risk perception had a negative but nonsignificant effect. Simultaneously, both variables affect purchasing decisions, with trust dominating. These findings indicate that students tend to rely more on trust than on risk assessment in online transactions. From a behavioral economics perspective, this shows a tendency toward decision-making that is not entirely rational, in which ease, experience, and subjective perception play important roles. This research contributes to the study of digital marketing economics and its practical implications for businesspeople seeking to build consumer trust.